Comparison of Solvency Levels and Claim Payment Ability of PT Asuransi Dayin Mitra Tbk and PT Asuransi Jasa Tania Tbk Amidst 2023 Economic Conditions - Erlina Waruwu; Dyah Palupiningtyas (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze the comparison of solvency levels and claim payment abilities between two general insurance companies in Indonesia, PT Asuransi Dayin Mitra Tbk (ASDM) and PT Asuransi Jasa Tania Tbk (ASJT), considering the macroeconomic conditions in 2023. The methods used are qualitative and quantitative comparative analyses based on the audited financial statements and annual reports of both companies, as well as a review of macroeconomic data from official sources. The findings indicate that ASDM and ASJT managed to achieve positive performance despite economic challenges, with ASJT recording higher growth in premiums and net income. Both companies maintained solvency ratios above regulatory thresholds and controlled claims ratios. Business strategy adaptation, sound governance, and effective risk management contributed to these achievements. Macroeconomic factors such as inflation, interest rates, and exchange rates were found to influence the performance of both companies, with varying levels of sensitivity depending on their market segment focus. These findings provide valuable insights into the dynamics of the insurance business in Indonesia and highlight opportunities and challenges that industry stakeholders need to anticipate..